Facile and controllable synthesis of BaCO3 crystals superstructures using a CO2-storage material - Feng Sha; Bo Guo; Jing Zhao; Fei Zhang; Xianshu Qiao; Liang Ma; Chang Liu; Jianbin Zhang (Green Energy & Environment, 2017)
We here report a new CO2 capture and storage method that converts CO2 into a novel alkyl carbonate salt, denoted as CO2SM, by a system consisting of equimolar 1,4-butanediol (BDO) and 1,2-ethylenediamine (EDA). This novel CO2SM was then used to prepare BaCO3 crystals through a simple and fast hydrothermal synthesis under mild conditions. The CO2SM was both the source of CO2 and the modifier to regulate the nucleation and growth of BaCO3 crystals. The morphology of the BaCO3 crystals could be tuned from rod to shuttle by adjusting the key influencing factors, including CO2SM concentration, mineralization temperature, and mineralization time. A possible mechanism for the synthesis of BaCO3 crystals from the CO2SM was also presented. After the BaCO3 crystals were isolated, the filtrate of the hydrothermal reaction could be recycled to again absorb CO2 and prepare BaCO3 crystals of the same polymorph. This novel approach appears promising for preparing well-formed metal carbonates. Keywords: BaCO3, CO2-storage material, Morphology control, CO2 capture and utilization